PERAN PEMERINTAH DAERAH DALAM MEMBERDAYAKAN UMKM DI KOTA SEMARANG (STUDI KASUS KAMPUNG BATIK KOTA SEMARANG) - Giovanni Malemta Purba; Purwoko . (Journal of Politic and Government Studies, 2018)
Micro, Small and Medium Enterprises (MSMEs) themselves are an important part of the economy of a country or region, not least in the city of Semarang itself. Semarang City is one of the big cities in Indonesia which is the capital city of the Central Java Province. Semarang itself is often known as an industrial city, trade and services. The city of Semarang itself is the capital of Central Java Province where this big city has a lot of potential based on its geographical and historical location. Semarang has a batik